Social Media, Messaging Apps, and Affective Polarization in the United States and Japan. Issue 5 (3rd September 2022) - Lee, Sangwon; Rojas, Hernando; Yamamoto, Masahiro
ABSTRACT: This study explores how emerging media platforms (i.e., social media and messaging apps) contribute to affective political polarization. We rely on cross-national data (USA and Japan), which allows us to explore the broader implications of how emerging media platforms contribute to political polarization in different cultural contexts. The results are very consistent; social media news use is positively related to affective polarization while messaging apps are negatively related in the USA and Japan. In addition, in the USA, the association of messaging app news and affective polarization is amplified by partisanship strength.